Formulation and in vitro /in vivo Evaluation of Silymarin Solid Dispersion- Based Topical Gel for Wound Healing - Malik, Bushra; Eman B. H. Al-Khedairy (Iraqi Journal of Pharmaceutical Sciences, 2023)
Silybum marianum, from which silymarin (SM) is extracted, is a medicinal herb. In the Biopharmaceutics Classification System, it is of the class II type, meaning it is almost completely insoluble in water. It has a number of therapeutic properties, including anti-inflammatory as well as properties that promote wound healing.This research target is to promote the dissolution and solubility of SM by employing a technique called solid dispersion and then incorporating the formula of solid dispersion into a topical gel that can be used for wound healing. Solid dispersion is a technique used to enhance solubility and dissolve pharmaceuticals that are not water-soluble. This method is widely used because of its low cost and high efficiency. Because of its capacity to repair skin, the hydrophilic carrier nicotinamide (NA) was selected in this investigation as the  carrier. Kneading, solvent evaporation and fusion  with a consistent drug-to-carrier ratio were the three separate processes utilized in the preparation of solid dispersion (1:1, 1:3, and 1:5). In addition, the products were examined to determine their physical characteristics and the degree of crystallinity. The selected formula was combined into a hyaluronic acid base gel using the cold method. This gel was then evaluated in vitro for physical qualities and put to an in vivo (animal) examination to determine how it healed wounds.The study found that the solvent evaporation made SM 25 times more soluble and caused all of it to be released in 20 minutes for a 1:3 ratio. Additional research using DSC and XRD demonstrated the amorphous nature of the result. According to FTIR, there was no evidence of interaction between the two.The gel formula had good qualities, like a pH of 6.6, good spreadability, and drug release within three hours. It also contributed to the rapid healing of wounds.